The PRC considers military AI ethics: Can autonomy be trusted? - Metcalf, Mark (Frontiers in Big Data, 2022)
China’s People’s Liberation Army (PLA) is currently wrestling with the benefits and challenges of using artificial intelligence (AI) to enhance their capabilities. Like many other militaries, a key factor in their analysis is identifying and dealing with the ethical implications of employing AI-enabled systems. Unlike other militaries, however, as the PLA is directly controlled by the Chinese Communist Party (CCP), such considerations are conspicuously influenced by a definition of military ethics that is fundamentally political. This Mini-Review briefly discusses key tenets of PLA military ethics and then investigates how the challenges of military AI ethics are being addressed in publicly-available government and PLA publications. Analysis indicates that, while the PLA is considering AI ethical challenges that are common to all militaries (e.g., accountability), their overriding challenge that they face is ‘squaring the circle’ of benefitting from autonomous AI capabilities while providing the CCP with the absolute control of the PLA that it demands – which is, from the CCP’s perspective, a military ethics consideration.